Endometriosis diagnosis, staging and typology and adverse pregnancy outcome history. Issue 6 (16th May 2022) - Schliep, Karen C.; Farland, Leslie V.; Pollack, Anna Z.; Buck Louis, Germaine; Stanford, Joseph B.; Allen‐Brady, Kristina; Varner, Michael W.; Kah, Kebba; Peterson, C. Matthew
Abstract: Background: Women with endometriosis may have an increased risk of adverse pregnancy outcomes. Research has focused on infertility clinic populations limiting generalisability. Few studies report differences by endometriosis severity. Objectives: We investigated the relationships between endometriosis diagnosis, staging and typology and pregnancy outcomes among an operative and population‐based sample of women. Methods: Menstruating women ages 18–44 years enrolled in the ENDO Study (2007–2009), including the operative cohort: 316 gravid women undergoing laparoscopy/laparotomy at surgical centres in Utah and California; and the population cohort: 76 gravid women from the surgical centres' geographic catchment areas. Pregnancy outcomes were ascertained by questionnaire and included all pregnancies prior to study enrolment. Endometriosis was diagnosed via surgical visualisation in the operative cohort and pelvic magnetic resonance imaging in the population cohort. Adjusted prevalence ratios (aPR) and 95% confidence intervals (CI) were estimated using generalised linear mixed models for pregnancy outcomes, adjusting for women's age at study enrolment and at pregnancy, surgical site, body mass index and lifestyle factors. Results: Women in the operative cohort with visualised endometriosis ( n = 109, 34%) had a lower prevalence of live births, aPR 0.94 (95% CI 0.85, 1.03) and a higher prevalence of miscarriages, aPR 1.48 (95% CI 1.23, 1.77) compared with women without endometriosis. The direction and magnitude of estimates were similar in the population cohort. Women with deep endometriosis were 2.98‐fold more likely (95% CI 1.12, 7.95) to report a miscarriage compared with women without endometriosis after adjusting for women's age at study enrolment and at pregnancy, surgical site and body mass index. No differences were seen between endometriosis staging and pregnancy outcomes. Conclusions: While there was no difference in number of pregnancies among women with and without endometriosis in a population‐based sample, pregnancy loss was more common among women with endometriosis, notably among those with deep endometriosis.